Using reflection journal to evaluate student's responses to problem-based learning for first year chemical engineering students - Sadikin, Aziatul Niza (2013)
Introduction to Engineering (ITE) is a first year course in the Faculty of Chemical Engineering, Universiti Teknologi Malaysia that fully implements problem-based learning (PBL) approach since the past four years. For year 2012, the problem for the course was designed by Iskandar Regional Development Authority on Low Carbon Society. It is a real case study based on one of the main agendas of the IRDA, which is to decrease carbon emission in Iskandar Malaysia region through resources conservation. In PBL, besides case study design, one of the most important elements is the assessment part. Students’ assessment in PBL is more challenging compared to conventional lecture in which examination is the sole indicator of students’ performance. In PBL, students’ involvement in the learning process itself is also evaluated through i.e. presentation, peer teaching as well as reflection journal. This paper discusses the role of reflection journal and how it helps students’ learning in PBL environment. Analysis of reflection journals prepared by 32 students throughout the ITE course found that reflection journal is a powerful assessment tool as it allows lecturers to get into what the students have been through throughout the course deeply. The students are not only reflecting the technical content of the course, but also willing to share their thoughts emotionally from different perspectives – as student, team member, group leader, member of society etc. Also through reflection journal, students are able to develop a lot of skills including communication, problem solving, critical thinking and life-long learning.